Case Report: Post-Partum Complications of NFκB1 Deficiency Underscore a Need to Better Understand Primary Immunodeficiency Management During Pregnancy - Nguyen, Diem-Tran I.; Grimes, Amanda; Mahoney, Donald; Faro, Sebastian; Shearer, William T.; Miller, Aaron L.; Rider, Nicholas L. (Frontiers in Pediatrics, 2021)
Nuclear factor κappa-B (NFκB) is a family of transcription factors involved in regulating inflammation and immunity. Mutations in the NFκB1 pathway are associated with primary immune defects and underlie the most common monogenic etiology of common variable immunodeficiency (CVID). However, little is known about how NFκB1 defects or primary immunodeficiency (PID) complicate pregnancy. We present a previously healthy 34-year-old patient who suffered from poor wound healing and sterile sepsis during the postpartum period of each of her three pregnancies. She was otherwise asymptomatic but her daughter developed Evans Syndrome (ES) with hypogammaglobulinemia prompting expanded genetic testing which revealed a novel monoallelic variant in NFκB1. This case highlights that pregnancy-related complications of PID can be difficult to recognize and may portend adverse patient outcomes. For these reasons, guidance regarding diagnosis and management of women of childbearing age with PID is warranted.